Upaya Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Keyboard Menggunakan Metode Drill - Gia Lara Dristiana; Jagar Lumbantoruan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Before the class action is carried out, a pre-cycle is first carried out where the student’s abilities are still far from what is expected, therefore the researcher aims to overcome this through action in the type of classroom action research with the steps of planning, action, observation and reflection.The results showed that student learning outcomes improved significantly after using the Drill method in class XI Music. The learning flow in the first cycle is the practice of playing scales, playing songs gradually, for example phrase by phrase, fingering the right and left hands in slow, medium and fast tempos. Student learning achievement in cycle I, 9 students who increased (75%), and 4 students who still did not improve (25%).Based on the percentage of achievement, the first cycle is categorized as good. Because there are still some students who have not been completed, the researcher reflects with the teacher who observes to overcome the still existence of students who have not experienced significant improvement, the solution made by the researcher is to control more students in playing the keyboard. Then continued in cycle II, in cycle II carried out fingering exercises again, smooth right hand and left hand. After being carried out in the second cycle, Alhamdulillah, 13 students have increased significantly, and there are no students who are incomplete.